On the 100th Anniversary of the Full Member of Russian Academy Of Sciences L.V. Ovsyannikov and the 80th Anniversary of His Follower, Professor N.H. Ibragimov - Emelyanova, Inna (Journal of Vibration Testing and System Dynamics, 2026)
Two dates coincided in 2019: the centenary of the full member of Russian Academy of Sciences Lev Vasilievich Ovsyannikov (April 22, 1919 – May 23, 2014) and the eightieth anniversary of his follower, professor Nail Hairullovich Ibragimov (January 18, 1939 – November 04, 2018). Through the efforts of them and their numerous students and followers, Sophus Lie’s theory of local transformation groups was revived and received promising development.